Upaya Meningkatkan Membaca Huruf Hijaiyah Melalui Penggunaan Media Flash card Untuk Anak Usia Dini - Rini Marlina (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This study aims to improve the ability to read hijaiyah letters in early childhood through the use of flash card media in Kindergarten.B Berkah Al Qudsyiah. This study uses the Classroom Action Research (PTK) method which is carried out in two cycles with four stages, namely planning, implementation, observation, and reflection. The research subjects amounted to 17 children in group B. Data were collected through observation and analyzed descriptively quantitatively. Pre-cycle results showed that most children were in the undeveloped category in the ability to mention and read a series of hijaiyah letters. After the action in cycle I, there was an increase although there were still children who had not reached the optimal category. Improvements were made in cycle II through intensive repetition, variations of games with flash cards, and providing motivation. The results showed a significant increase, the majority of children were able to mention and read hijaiyah letters in the developing as expected and developing very well categories, and there were no more children in the undeveloped category. Thus, the use of flash card media is proven effective to improve the ability to read hijaiyah letters while creating a more enjoyable learning atmosphere for early childhood.